(untitled) (Journal of Dhaka National Medical College & Hospital, 2020)
Background: Vitamin B12 deficiency may remain latent in the early phase of hypothyroidism. Symptoms of neuropathy may occur due to combination of deficiency of thyroxin & vitamin B12 in newly diagnosed hypothyroid female patients. Objectives: To assess the prevalence and clinical features of vitamin B12 deficiency in newly diagnosed hypothyroid female patients in Dhaka. Methods: This cross-sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC) between July’ 2015 to June’ 2016 on 80 newly diagnosed hypothyroid female patients with clinical features of vitamin B12 deficiency. Their serum TSH, FT4, FT3 levels were estimated for assessment of thyroid function status by ELISA method. Vitamin B12 level was also estimated to observe its level by using standard method. The statistical analysis was done by ANOVA test, paired, independent sample’t’ test. Results: In this study, a total 80 newly diagnosed hypothyroid female patients were evaluated among them 34 patients had low vitamin B12 level. Generalized weakness, impaired memory, depression, numbness and decreased reflexes were more frequently noted in vitamin B12 deficient patient. Additionally 16 subjects were complained of symptoms consistent with vitamin B12 deficiency, but had normal range of vitaminB12 level. Conclusion: The present study revealed that there is a high (approx 42.5%) prevalence of vitamin B12 deficiency in newly diagnosed hypothyroid female patients. Traditional symptoms are not a good guide to determining presence of vitamin B12 deficiency. Screening for vitamin B12 level should be undertaken in all newly diagnosed hypothyroid female patients. Background: Vitamin B12 deficiency may remain latent in the early phase of hypothyroidism. Symptoms of neuropathy may occur due to combination of deficiency of thyroxin & vitamin B12 in newly diagnosed hypothyroid female patients. Objectives: To assess the prevalence and clinical features of vitamin B12 deficiency in newly diagnosed hypothyroid female patients in Dhaka. Methods: This cross-sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC) between July’ 2015 to June’ 2016 on 80 newly diagnosed hypothyroid female patients with clinical features of vitamin B12 deficiency. Their serum TSH, FT4, FT3 levels were estimated for assessment of thyroid function status by ELISA method. Vitamin B12 level was also estimated to observe its level by using standard method. The statistical analysis was done by ANOVA test, paired, independent sample’t’ test. Results: In this study, a total 80 newly diagnosed hypothyroid female patients were evaluated among them 34 patients had low vitamin B12 level. Generalized weakness, impaired memory, depression, numbness and decreased reflexes were more frequently noted in vitamin B12 deficient patient. Additionally 16 subjects were complained of symptoms consistent with vitamin B12 deficiency, but had normal range of vitaminB12 level. Conclusion: The present study revealed that there is a high (approx 42.5%) prevalence of vitamin B12 deficiency in newly diagnosed hypothyroid female patients. Traditional symptoms are not a good guide to determining presence of vitamin B12 deficiency. Screening for vitamin B12 level should be undertaken in all newly diagnosed hypothyroid female patients. Background: Vitamin B12 deficiency may remain latent in the early phase of hypothyroidism. Symptoms of neuropathy may occur due to combination of deficiency of thyroxin & vitamin B12 in newly diagnosed hypothyroid female patients. Objectives: To assess the prevalence and clinical features of vitamin B12 deficiency in newly diagnosed hypothyroid female patients in Dhaka. Methods: This cross-sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC) between July’ 2015 to June’ 2016 on 80 newly diagnosed hypothyroid female patients with clinical features of vitamin B12 deficiency. Their serum TSH, FT4, FT3 levels were estimated for assessment of thyroid function status by ELISA method. Vitamin B12 level was also estimated to observe its level by using standard method. The statistical analysis was done by ANOVA test, paired, independent sample’t’ test. Results: In this study, a total 80 newly diagnosed hypothyroid female patients were evaluated among them 34 patients had low vitamin B12 level. Generalized weakness, impaired memory, depression, numbness and decreased reflexes were more frequently noted in vitamin B12 deficient patient. Additionally 16 subjects were complained of symptoms consistent with vitamin B12 deficiency, but had normal range of vitaminB12 level. Conclusion: The present study revealed that there is a high (approx 42.5%) prevalence of vitamin B12 deficiency in newly diagnosed hypothyroid female patients. Traditional symptoms are not a good guide to determining presence of vitamin B12 deficiency. Screening for vitamin B12 level should be undertaken in all newly diagnosed hypothyroid female patients. J. Dhaka National Med. Coll. Hos. 2020; 26 (02): 20-22